The Belarusian-Russian Military Alliance in the Context of the Geostrategic Importance of Belarus for Russia as a Way to the West and Its Role in Achieving Its Geopolitical Goals (Part 1) - Bazyur, Grzegorz (Mediaforum : Analytics, Forecasts, Information Management, 2021)
This article by Grzegorz Baziur concerns the geostrategic importance of Belarus in the context of the „Russian road to the West” in the light of the neo-imperial policy of the Russian Federation, implemented by the authorities under the leadership of President Vladimir Putin. In the introduction, the author presented the aims of the article, research methods and his theses, and in the first part he described Belarusian-Russian relations in terms of military cooperation and the Russian vision of security policy in the West. In the last part of the text, the author asks the question - is there anything to fear from Belarus in the context of the Belarusian-Russian alliance under Russia’s hegemony? In this part, he discusses the meanders of Polish-Belarusian relations with Russia in the background, and the whole article concludes with conclusions on the security perspectives of Belarus and its neighboring countries, including Poland.